2021
DOI: 10.31235/osf.io/b9f2w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Influencing Asia-Pacific Countries’ Success Level in Curbing COVID-19: A Review Using a Social–Ecological System (SES) Framework

Abstract: Little attention has been paid to the impacts of institutional–human–environment dimen-sions on the outcome of Coronavirus disease 2019 (COVID-19) abatement. Through the diagnosticsocial–ecological system (SES) framework, this review paper aimed to investigate what and howthe multifaceted social, physical, and governance factors affected the success level of seven selectedAsia-Pacific countries (namely, South Korea, Japan, Malaysia, Singapore, Vietnam, Indonesia, andNew Zealand) in combatting COVID-19. Drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Furthermore, the socioeconomic status is higher when the education level is higher, and the higher education level can be a protective factor against the wrong information about the vaccination programs [32]. Similar results were found in many other studies, in Saudi Arabia, older age groups and education level were significantly associated with the vaccine acceptance, in other Arab community, males were more willing to accept the vaccine [33].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the socioeconomic status is higher when the education level is higher, and the higher education level can be a protective factor against the wrong information about the vaccination programs [32]. Similar results were found in many other studies, in Saudi Arabia, older age groups and education level were significantly associated with the vaccine acceptance, in other Arab community, males were more willing to accept the vaccine [33].…”
Section: Discussionsupporting
confidence: 83%
“…Although governance is an important factor in influencing a country's success in combating the pandemic, socioeconomic status is also insightful as it helps policymakers to develop strategies and measures to protect their country currently and in the future. 45 When a country healthcare system is at maximum capacity (e.g., Bosnia, Pakistan, India), the legitimacy of the government is challenged (e.g., Egypt), and with trust issues between the government and other actors, 46 finding the true values of COVID-19 statistics will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that the rapid response in introducing stay-at-home orders is important to reduce the impacts of COVID-19 [ 31 ], and case isolation and effective contact tracing can, within three months, control an outbreak of COVID-19 [ 32 ]. Additionally, high-q facilities, comprehensive COVID-19 testing policies, strict lockdown measures, penalties, and high level of trust towards the government seemed to be significant in determining the severity of COVID-19 severity [ 33 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“… Interviews Kerala's long-term investment in democratic local government and arrangements for incorporating women within grassroots state functions have built a high degree of public trust and cooperation with state actors, while local authorities embrace an ethic of care in the implementation of state responses. [ 33 ] What and how the multifaceted social, physical, and governance factors affected the success level of seven selected Asia-Pacific countries (South Korea, Japan, Malaysia, Singapore, Vietnam, Indonesia, and New Zealand) in combatting COVID-19? Content analysis High facility adequacy, comprehensive COVID-19 testing policies, strict lockdown measures, penalties, and high level of trust towards the government seemed to be significant in determining the COVID-19 severity in a country.…”
Section: Literature Reviewmentioning
confidence: 99%